2013
DOI: 10.1371/journal.pone.0065882
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activations during Visual Sequence Learning Leave a Trace in Post-Training Spontaneous EEG

Abstract: Recent EEG studies have shown that implicit learning involving specific cortical circuits results in an enduring local trace manifested as local changes in spectral power. Here we used a well characterized visual sequence learning task and high density-(hd-)EEG recording to determine whether also declarative learning leaves a post-task, local change in the resting state oscillatory activity in the areas involved in the learning process. Thus, we recorded hd-EEG in normal subjects before, during and after the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
8
36
1
Order By: Relevance
“…Also, we have previously found that alpha and theta modulation changed during the learning of a visual sequence (Moisello et al. ). Interestingly, the changes in movement‐related beta modulation reported in this study were not clearly associated with improved performance: although movement speed increased in the 40‐minute practice in both groups, we did not find significant correlation between ERS beta changes and the decrease in movement time, in agreement with the results of recent studies (Tan et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, we have previously found that alpha and theta modulation changed during the learning of a visual sequence (Moisello et al. ). Interestingly, the changes in movement‐related beta modulation reported in this study were not clearly associated with improved performance: although movement speed increased in the 40‐minute practice in both groups, we did not find significant correlation between ERS beta changes and the decrease in movement time, in agreement with the results of recent studies (Tan et al.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, they were interpreted as signs of use‐dependent plasticity, possibly independent from learning outcomes (Moisello et al. ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…To minimize trial rejection from frequent blinks, data were segmented into relatively short epochs extending from −100 ms to 800 ms relative to stimulus onset, spanning just half of the inter-stimulus interval. Changes in spectral power during learning and signatures of prior learning in resting-state data recorded after completion of the task in Experiment I have been reported in a separate article (Moisello et al, 2013). The present study focused on event-related potentials elicited by the sequence elements.…”
Section: Methodsmentioning
confidence: 76%
“…Rushby et al, 2002; Wiswede et al, 2007). Some studies have examined spectral changes exhibited after versus before learning (Moisello et al, 2013), or more finely over the course of repeated presentations (Madhaven et al, 2015; Zhuang et al, 1997), in the latter cases linking the changes to motor execution (Zhuang et al, 1997), or memory retrieval (Madhaven et al, 2015) rather than memory formation. To our knowledge, however, no study has yet fully exploited the possibilities outlined above, and tracked neural correlates of memory formation on an element-by-element basis as they develop through discrete learning state transitions.…”
Section: Introductionmentioning
confidence: 99%